Identification and characterization of fluid escape structures (pockmarks) in the Estremadura Spur, West Iberian Margin - Duarte, Debora (2018)
Located on the West Iberian margin, between Cabo Carvoeiro and Cabo da Roca, the Estremadura Spur is a trapezoidal promontory elongated in an east-west direction, extending until the Tore seamount. Recently a field with more than 70 pockmarks was discovered in the NW region of the Estremadura Spur outer shelf (Lourinhã Monocline). Pockmarks are the seabed culminations of fluid migration through the sedimentary column and their characteristic seabed morphologies correspond to cone-shaped circular or elliptical depressions. The characterization of these features and the understanding of the associated fluid escape process are the main objectives of this work. Here we characterize these structures to understand their structural and stratigraphic control based on: 1) Seismic processing and interpretation of the high resolution 2D single-channel sparker seismic dataset, 2) Bathymetric and Backscatter interpretation and 3) ROV direct observation of the seafloor. The analysis of the seismic profiles allowed the identification of six seismic units, disturbed by the migration and accumulation of fluids. The Estremadura Spur outer shelf has been affected by several episodes of fluid migration and fluid escape during the Pliocene-Quaternary that are expressed by a vast number of seabed and buried pockmarks. At present, the pockmarks are mainly inactive, as the seabed pockmarks are covered by recent sediments. It is concluded that the migration of fluids to the seabed occurred over the Pliocene-Quaternary, as indicated by the buried pockmarks at different depths below the seabed. The vertical stacking of various pockmarks suggests a cyclical fluid flow activity that can possibly be the result of the eustatic sea level variations and the subsequent changes of the hydrostatic pressure.